2015
DOI: 10.1111/gcb.12878
|View full text |Cite
|
Sign up to set email alerts
|

Climate change enhances primary production in the western Antarctic Peninsula

Abstract: Intense regional warming was observed in the western Antarctic Peninsula (WAP) over the last 50 years. Here, we investigate the impact of climate change on primary production (PP) in this highly productive region. This study is based on temporal data series of ozone thickness (1972-2010), sea ice concentration (1978-2010), sea-surface temperature (1990-2010), incident irradiance (1988-2010) and satellite-derived chlorophyll a concentration (Chl-a, 1997-2010) for the coastal WAP. In addition, we apply a photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 82 publications
3
74
0
1
Order By: Relevance
“…Similar results for annually integrated NPP in the WAP have recently been reported by Moreau et al . []. Years with more ice‐free days and higher ANCP display higher midsummer NCP (e.g., 2005 and 2006) (Figure ), suggesting that other factors (e.g., iron and light) preconditioned by or associated with the length of the growing season have ramifications throughout the growing season.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results for annually integrated NPP in the WAP have recently been reported by Moreau et al . []. Years with more ice‐free days and higher ANCP display higher midsummer NCP (e.g., 2005 and 2006) (Figure ), suggesting that other factors (e.g., iron and light) preconditioned by or associated with the length of the growing season have ramifications throughout the growing season.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, earlier retreat and delayed advance of sea ice has resulted in a 3 month lengthening of the summer ice-free season in the Amundsen and Bellingshausen Seas . While this extension of the ice-free period was expected to increase annual phytoplankton production and growth (Sarmiento et al, 2004;Moreau et al, 2015), no such trend has yet been observed Montes-Hugo et al, 2008). This may be due to constraints imposed by nutrient and light limitation that are also key drivers of phytoplankton growth in the SSIZ Westwood et al, 2010).…”
Section: Seasonal Sea Ice Zonementioning
confidence: 98%
“…Glacial melt has resulted in an influx of fresh water to coastal regions of the WAP, freshening and increasing the stratification of surface waters over the summer. While phytoplankton productivity is expected to increase with increasing sea surface temperature (Rose et al, 2009), the phytoplankton community is likely to be more affected by resultant changes in SIE and freshwater inputs to the CZ (Arrigo et al, 2015;Moreau et al, 2015).…”
Section: West Antarcticamentioning
confidence: 99%
See 2 more Smart Citations